2019
DOI: 10.1007/s11222-019-09903-y
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Monte Carlo with transformations

Abstract: This paper introduces methodology for performing Bayesian inference sequentially on a sequence of posteriors on spaces of different dimensions. We show how this may be achieved through the use of sequential Monte Carlo (SMC) samplers (Del Moral et al., 2006, making use of the full flexibility of this framework in order that the method is computationally efficient. In particular, we introduce the innovation of using deterministic transformations to move particles effectively between target distributions with di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…We cannot expect SMC samplers that rely on MCMC kernels to perform well when these kernels have poor mixing properties. This has motivated the use of other non-equilibrium dynamics [Vaikuntanathan and Jarzynski, 2008, Heng et al, 2015, Bernton et al, 2019a, Everitt et al, 2020. There are some studies on the advantages of interacting particle methods over Markov chains on multimodal targets [Schweizer, 2012b, Paulin et al, 2019.…”
Section: Discussionmentioning
confidence: 99%
“…We cannot expect SMC samplers that rely on MCMC kernels to perform well when these kernels have poor mixing properties. This has motivated the use of other non-equilibrium dynamics [Vaikuntanathan and Jarzynski, 2008, Heng et al, 2015, Bernton et al, 2019a, Everitt et al, 2020. There are some studies on the advantages of interacting particle methods over Markov chains on multimodal targets [Schweizer, 2012b, Paulin et al, 2019.…”
Section: Discussionmentioning
confidence: 99%
“…This reasoning also applies to mixture models and clustering, for which a labelling of components may be introduced in order to avoid identifiability problems with the parameters of interest. We have noted some of these aspects in Everitt et al (2016), where ordering of components leads to the aforementioned intractability of the joint proposal q.…”
Section: Motivationmentioning
confidence: 99%
“…The SMCS algorithm is a generalization of the particle filter (Sanjeev Arulampalam et al 2002;Doucet and Johansen 2009) for dynamic state estimation, generating weighted samples from the posterior distribution. Since the SMCS algorithm was proposed in Del Moral et al (2006), considerable improvements and extensions of the method have been proposed, such as Fearnhead and Taylor (2013), Beskos et al (2017), Heng et al (2020), Everitt et al (2020), and more information on the developments of the SMCS methods can be found in the recent reviews (Dai et al 2020;Chopin and Papaspiliopoulos 2020). We also note here that there are other parameter estimation schemes also based on particle filtering, e.g., Gilks and Berzuini (2001), Chopin (2002), and the differences and connections between SMCS and these schemes are discussed in Del Moral et al (2006).…”
Section: Introductionmentioning
confidence: 99%